2014
DOI: 10.1007/s10926-014-9521-x
|View full text |Cite
|
Sign up to set email alerts
|

Healing or Harming? Healthcare Provider Interactions with Injured Workers and Insurers in Workers’ Compensation Systems

Abstract: Injured workers with long term complex injuries experience difficulties with healthcare in the workers' compensation context. Changes in insurer administrative demands and compensation processes could increase HCP participation and job satisfaction. This in turn may improve injured worker recovery. Further research into experiences of distinct healthcare professions with workers' compensation systems is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 52 publications
2
43
1
Order By: Relevance
“…A recent paper about the scheme argued that ‘in spite of an abundance of government recommendations and scholarly evidence prioritising timely return to work for injured workers, the NSW Workers’ Compensation Scheme systematically fails to support this objective’ [26]. The interaction between HCP and the claims managers in the workers’ compensation scheme has been found challenging [27]. It seems that, besides or before implementing an EBM tool, the interaction between HCP and claims managers, and claims manager training should be improved.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper about the scheme argued that ‘in spite of an abundance of government recommendations and scholarly evidence prioritising timely return to work for injured workers, the NSW Workers’ Compensation Scheme systematically fails to support this objective’ [26]. The interaction between HCP and the claims managers in the workers’ compensation scheme has been found challenging [27]. It seems that, besides or before implementing an EBM tool, the interaction between HCP and claims managers, and claims manager training should be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that access to healthcare for IW may be negatively affected by physician aversion to the gatekeeping role [Ison, ; Lax and Manetti, ; Lippel, ; MacEachen et al, ; Kilgour et al, ,], including bureaucratic requirements [Kosny et al, ; Kilgour et al, ] and increased scrutiny [MacEachen et al, ], that sometimes affects their treatment choices because of the need to provide “objective findings” [Ison, ; Lax, ]. A study of Ontario doctors treating patients covered by WC found they resented the time required to complete the forms, the repeated requests for more and more precise evaluations and being ignored after providing advice on treatment or functional abilities [MacEachen et al, ], findings confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have examined the workers’ perception of the compensation process [Kilgour et al, ] only a few have specifically focused on the experience of doctors involved in compensation systems [Kosny et al, ; Murgatroyd et al, ; Kilgour et al, ; Brijnath et al, ], or in sickness absence certification [Gerner and Alexanderson, ].…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, compensation schemes are based on mechanism of injury and/or type of disability, and/or governing legislation to access financial entitlements. Notwithstanding that, themes from qualitative research appear to be consistent across jurisdictions and countries [21, 22]. Further, increased BMI has been associated with greater absenteeism, healthcare costs and claim rates across numerous jurisdictions, albeit in larger cohorts [55, 56].…”
Section: Discussionmentioning
confidence: 99%